2014
DOI: 10.5604/20831862.1099047
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between the Number of Repetitions Performed at Given Intensities Is Different in Endurance and Strength Trained Athletes

Abstract: Prescribing training intensity and volume is a key problem when designing resistance training programmes. One approach is to base training prescription on the number of repetitions performed at a given percentage of repetition maximum due to the correlation found between these two measures. However, previous research has raised questions as to the accuracy of this method, as the repetitions completed at different percentages of 1RM can differ based upon the characteristics of the athlete. The objective of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
92
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(108 citation statements)
references
References 29 publications
(38 reference statements)
5
92
0
5
Order By: Relevance
“…However, some research has found that the number of repetitions completed showed a positive relationship with the number of capillaries per mm 2 of muscle cross-sectional area [28], and a negative correlation with the percentage of type II fibers [5]. Therefore, it appears that the large variability observed in the number of repetitions completed against a given load ( %1RM) may depend, at least in part, on the specific muscle characteristics and training background of each participant [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, some research has found that the number of repetitions completed showed a positive relationship with the number of capillaries per mm 2 of muscle cross-sectional area [28], and a negative correlation with the percentage of type II fibers [5]. Therefore, it appears that the large variability observed in the number of repetitions completed against a given load ( %1RM) may depend, at least in part, on the specific muscle characteristics and training background of each participant [21].…”
Section: Discussionmentioning
confidence: 99%
“…Neste estudo os autores verificaram que levantadores de peso executaram menos repetições até a exaustão com as intensidades de 70 e 80% de 1-RM, no exercício leg press, do que corredores, que possuem uma força máxima em torno de 50% menor do que os levantadores de peso. [9] Esse achado pode ser parcialmente explicado pela variação da força máxima entre nossos voluntários, os quais apresentaram cargas para o teste de 1-RM entre 64,0 kg (máximo) e 30 kg (mínimo) . Apesar de todos serem habituados ao TR, sujeitos mais fortes podem ter realizado mais testes e treinos com cargas próximas a máxima, o que os coloca em melhores condições de atingirem altos níveis de força, fazendo com que a carga absoluta utilizada no teste de repetição máxima fosse estressante em função de serem mais familiarizados a testes de força máxima, levando, consequentemente a uma exaustão antecipada.…”
Section: Discussionunclassified
“…It has been reported that hypoxic muscle training is effective for improving muscle strength and that aerobic muscle training is effective for improving muscle endurance [9]. On the other hand, Kon et al…”
Section: Effectiveness Of Trainingmentioning
confidence: 97%
“…On the other hand, aerobic exercise, which is training under a condition with a high oxygen concentration in muscle, is effective for increasing the endurance of muscles, which is persistence of muscle activity [9].…”
Section: Introductionmentioning
confidence: 99%